Job Search Requirements, Effort Provision and Labor Market Outcomes - Patrick Arni; Amelie Schiprowski (Center for Economic Studies and ifo Institute (CESifo), 2018)
How effective are effort targets? This paper provides novel evidence on the effects of job search requirements on effort provision and labor market outcomes. Based on large-scale register data, we estimate the returns to required job search effort, instrumenting individual requirements with caseworker stringency. Identification is ensured by the conditional random assignment of job seekers to caseworkers. We find that the duration of un- and non-employment both decrease by 3% if the requirement increases by one monthly application. When instrumenting actual applications with caseworker stringency, an additionally provided monthly application decreases the length of spells by 4%. In line with theory, we further find that the effect of required effort decreases in the individual's voluntary effort. Finally, the requirement level causes small negative effects on job stability, reducing the duration of re-employment spells by 0.3% per required application. We find a zero effect on re-employment wages.
Keywords: J64; J65; 330; effort targets; job search behavior; unemployment insurance; incentives